2008
DOI: 10.1007/s11689-008-9001-8
|View full text |Cite
|
Sign up to set email alerts
|

A solution to limitations of cognitive testing in children with intellectual disabilities: the case of fragile X syndrome

Abstract: Intelligence testing in children with intellectual disabilities (ID) has significant limitations. The normative samples of widely used intelligence tests, such as the Wechsler Intelligence Scales, rarely include an adequate number of subjects with ID needed to provide sensitive measurement in the very low ability range, and they are highly subject to floor effects. The IQ measurement problems in these children prevent characterization of strengths and weaknesses, poorer estimates of cognitive abilities in rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
144
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(148 citation statements)
references
References 23 publications
(21 reference statements)
4
144
0
Order By: Relevance
“…Including adaptive behaviour testing in the diagnosis, as achieved systematically only in Iceland, may decrease the number of falsely positive cases (thus wrongly considered with severe intellectual disability). 20,21 In spite of this, the highest prevalence was found in Iceland. This may be explained by the fact that the adaptive behaviour scores appear to be more important for those with higher intellectual scores, that is for those with mild intellectual disability, than for those with severe intellectual disability.…”
Section: Discussionmentioning
confidence: 97%
“…Including adaptive behaviour testing in the diagnosis, as achieved systematically only in Iceland, may decrease the number of falsely positive cases (thus wrongly considered with severe intellectual disability). 20,21 In spite of this, the highest prevalence was found in Iceland. This may be explained by the fact that the adaptive behaviour scores appear to be more important for those with higher intellectual scores, that is for those with mild intellectual disability, than for those with severe intellectual disability.…”
Section: Discussionmentioning
confidence: 97%
“…The variability in the strength and direction of phenotypic differences observed in the Fmr1 KO mouse may at first seem unsettling and worthy of discarding the model altogether. However, the heterogeneity of FXS is such that affected individuals exhibit a range of cognitive impairments, with affected males presenting with mild to severe cognitive symptoms (162,209). This poses a challenge for FXS animal models, but it also might be considered a strength.…”
Section: Discussionmentioning
confidence: 99%
“…IQ scores decrease over time, which is likely a result of delayed development in individuals with FXS (160,161). Novel approaches to intelligence testing have found that traditional IQ tests can be modified to reveal subtle differences within this select population (162). Starting with the Dutch-Belgium Fragile X Consortium, many researchers have conducted thorough characterizations of Fmr1 KO mice to compare their phenotypes to the intellectual disabilities displayed by individuals with FXS.…”
Section: Cognitive Deficitsmentioning
confidence: 99%
“…Their IQs tend to decline with age during childhood, and this is not the result of regression, but rather the failure to keep pace with the normal rate of intellectual development [10]. Intellectual functioning is defined as IQ.…”
Section: Discussionmentioning
confidence: 99%
“…Intellectual functioning is defined as IQ. This assessment is obtained through standardized, individually administered intelligence tests [10]. A major limitation of these tests is that they do not typically measure IQ below 40 or 50 [10], and previous observations in the literature have reported that only 15% of all males with FXS have IQ greater than or equal to 70% [7].…”
Section: Discussionmentioning
confidence: 99%